Prevalence and patterns of complementary and alternative medicine usage among adults with chronic kidney disease: A systematic review and meta-analysis - Chin, Jia Wen; Rafidah Abdullah; Tan, Benjamin Wei Wang; Wong, Koh Wei; Khor, Ban Hock (Elsevier B.V., 2025)
Background The use of complementary and alternative medicine (CAM) is common among individuals with underlying chronic illnesses. Objective This systematic review and meta-analysis investigated the global prevalence and patterns of CAM use among individuals with chronic kidney disease (CKD). Search strategy PubMed, Embase, and Cumulative Index to Nursing and Allied Health Literature Plus were searched from inception until 26th February 2024. Inclusion criteria Original articles reporting the use of at least one type of CAM among individuals aged above 18 years old and at all stages of CKD or undergoing any form of kidney replacement therapy. Data extraction and analysis Two independent reviewers performed the literature screening. The data were extracted from the included studies by one reviewer and cross-checked by another. Discrepancies were resolved by discussion and consensus among two reviewers. Primary information included prevalence of CAM use, types of CAM used, reasons for CAM use, factors associated with CAM use, and disclosure to healthcare providers. Meta-analyses were performed to determine the pooled prevalence of CAM use and non-disclosure of CAM using a random effect model. Results Forty-one studies were included in this systematic review and meta-analysis. The pooled prevalence of CAM use was 43% (95% confidence interval: 34%, 51%), I2 = 99.46%. The reasons for CAM use included treatment of underlying comorbidities, complications or symptoms, maintenance of general health, and treatment of CKD. Nutritional approaches were the most common CAM modality, with 412 different herbal and dietary supplements reported; psychological and physical approaches included massage therapy, relaxation techniques, and mind–body practices; and other complementary health approaches such as homeopathy, traditional Chinese medicine, and Ayurvedic medicine were also frequently reported. Factors associated with CAM use included sociodemographic characteristics such as older age, female gender, or higher income; disease or therapy factors such as not having diabetes, relying on hemodialysis, or poor adherence to medication; and patient or internal factors such as positive attitude towards CAM and perceived safety of CAM. About 66% (61%, 72%) of CAM users did not disclose the use of CAM to their healthcare providers. Conclusion CAM use is prevalent among individuals with CKD, and healthcare providers should communicate openly and effectively to emphasize the rational use of CAM to avoid potential harm. Please cite this article as: Chin JW, Abdullah R, Tan BWW, Wong KW, Khor BH. Prevalence and patterns of complementary and alternative medicine usage among adults with chronic kidney disease: A systematic review and meta-analysis. J Integr Med. 2025; Epub ahead of print.